Redesign The Traditional Folklore: Achieving A Sustainable Folklore For The Future Generation - Hedi Amelia Bella Cintya (ULTIMART Jurnal Komunikasi Visual, 2023)
Traditional folklore has experienced a decline in interest from generation to generation, leaving a significant question as to why younger generations are losing their interest in traditional tales. Despite the positive effects of traditional folklore on readers, this phenomenon calls for investigation. This study employs a descriptive-comparative preliminary investigation to address the decrease in interest in traditional folklore. Firstly, the present study aims to investigate the underlying reasons for the observed decline in the popularity of traditional folklore. Secondly, the study endeavors to comprehend the efforts undertaken by researchers and artists to counteract this waning interest. The previously identified determining factors will serve as guiding criteria to address the second research question. The ultimate outcome of this study will provide a comprehensive summary of the factors associated with the diminished appeal of traditional folklore among the younger generation, as well as the diverse attempts made by artists and researchers to rejuvenate this cultural heritage. Keywords: traditional; folklore; storytelling; descriptive study